Steam gasification of char derived from refuse-derived fuel pyrolysis: adsorption behaviour in phenol solutions - Sebe, Emese; Nagy, Gábor; Kállay, András Arnold (Environmental technology, 2024)
The increasing waste generation trends resulted in growing attention to the technologies that aim to reduce or prevent landfilling. The pyrolysis and gasification of refuse-derived fuel (RDF) allow waste to be turned into new raw materials, like pyrolysis gas and syngas. However, the wet gas cleaning processes result in the production of highly contaminated liquid waste. Phenolic compounds are common constituents of this wastewater and often appear in the wastewater of other industries as well. In this research, the laboratory-scale steam gasification of an RDF char was performed to produce syngas and adsorbent simultaneously. The RDF was previously pyrolyzed at 700 °C maximum temperature in a Hungarian pyrolysis pilot plant with approximately 120 kg h −1 capacity. In this thermal waste processing plant, the pyrolysis gas is already utilised by burning, but currently, the char ends up in landfills. The gasification of char samples was examined with different steam-to-carbon ratios (0.56, 0.84, and 1.12) and duration (30, 60, and 120 min) at 900 °C. Following gasification, the phenol removal capability of the solid by-products was investigated. The results show that its composition and energetic properties make the produced syngas more suitable to use as a raw material in the chemical industry rather than a fuel. At lower concentrations, the effectiveness of the solid by-product for phenol removal was comparable to commercial activated carbon. These are promising results about producing activated carbon from waste without any chemical treatment.